PENGARUH GAYA HIDUP, CITRA MEREK DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN PRODUK IPHONE DI KOTA BANJARMASIN - Alya Sofiyanti; Sugiharto; Nurul Wahyuni; Saladin Ghalib (Business Administration, FISIP ULM, 2024)
This study attempts to investigate, partially and concurrently, the effects of Lifestyle, Brand Image, and Product Quality on iPhone Product Purchase Decisions in Banjarmasin City. This study used multiple linear regression using SPSS version 26.0 to examine data from 75 respondents who were chosen through probability sampling approaches. The research was conducted utilizing quantitative methods with a causal explanatory research type. The study's findings indicate that while brand image and product quality have a somewhat substantial influence on purchasing decisions, lifestyle has no discernible impact. These three factors all have a strong impact on purchase decisions at the same time and have a strong correlation with one another